SUSTAINABLE ARCHITECTURAL DESIGN IN A TRADI-TIONAL BALINESE HOUSING IN ACCORDANCE TO THE CONCEPT OF TRI MANDALA - Ni Putu Aryani; Gunawan Tanuwidjaja (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2013)
Global challenges such as natural resource depletions, irregular weather pattern, and pollutions were imminent. The Home Green Design proposed by other countries was not suitable to Bali Island because of the local social context. The Balinese House is regulated with the Tri Mandala and Sanga Mandala to achieve the harmonious relations between Macrocosms (Bhuana Agung) and Microcosms (Bhuana Alit) [or Tri Hita Karana]. The Sanga Mandala guides the spatial pattern both on the house and the settlement scale. The Tenganan traditional Village implemented Tri-Mandala which organized the house into the Utama (upper and sacred), Madya (middle and human), and Nista (lower and profane). The Tri Mandala concept is very adaptable to the environment, even in the middle of the economic-driven activities and fast home development. However, the Tri-Mandala really supported the sustainability in the functionality aspect, the social acceptance aspect as well as thermal comfort aspect. Therefore, the Tri Mandala concept could be implemented in the contemporary house design in Bali.